Avaliação ultrassonográfica do sistema reprodutor feminino em codornas japonesas (Coturnix coturnix japonica) - Ribeiro, Catarina Brenha (2022)
Coturniculture is a segment of poultry production that is in increasing expansion, due to its growth characteristics and its attractive and nutritious products. In addition, the Japanese quail is an excellent experimental model, given its reproductive similarity to humans (such as chromosomal sex determination and the need for a constant temperature for oogenesis) and its embryos with greater manageability when compared to chicken. Therefore, the objective of this work was to verify the applicability of B-mode ultrasound (two-dimensional) in the reproductive system of Japanese quail (Coturnix coturnix japonica) and to compare it with the findings obtained by macroscopy. For this, 74 Japanese quails from the poultry sector of the Federal University of Lavras were used. Three birds were selected as a control group, which were periodically examined over a 24-hour period. The others were slaughtered every hour for a period of seven hours and, after that, 12, 16, 20, 21, 22 and 23 hours after laying. On ultrasound, the ovary was seen with the follicles in the form of concentric rings, the largest having 8 halos. The topography of the ovary was in the left abdominal cavity, cranial to the ventricle, with shape and contour dependent on the presence of follicles. The initial mean diameter of the primary follicle (F1) was 17.14 mm, ending with 27.28 mm on ultrasound, while the initial mean diameter of the secondary follicle (F2) was 15.00 mm, ending with 17.11 mm. The average diameter of the albumen had an initial value of 2.53 and a final diameter of 3.46 mm. It was observed that the albumen had an increasing growth curve, being interrupted only by the loss of ultrasound visualization. In a qualitative way, it was also possible to detect the ovary without follicles, in addition to changes in its shape during the trajectory in the oviduct and the presence of the perivitelline membrane. There was a linear effect between the data obtained from F1 by ultrasonography and by macroscopy, in addition to being possible to infer the position of the egg in the uterus by the size of the albumen. Ultrasonography is an auxiliary test capable of contributing to the diagnosis of reproductive disorders in birds, in addition to meeting demands and increasing productivity in laying quail flocks.